2011
DOI: 10.1002/app.35330
|View full text |Cite
|
Sign up to set email alerts
|

Imparting conductivity and chromic behavior on polyester fibers by means of poly(3‐methylthiophene) nanocoating

Abstract: Poly(3-methylthiophene) (P3MT)-coated polyester fabric is a conductive textile with specific electrical and optical properties; for instance, color change under external stimulus (chromic behavior) was successfully prepared by chemical polymerization with continuous, speed stirring technique. To investigate the striking effect of some variable conditions of polymerization process, the effect of reaction time, temperature, and oxidant concentration on conductivity of the P3MT-coated fabric was studied. Scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Moreover, no deformation was observed in the longitudinal image of the fiber. In the studies where PAn and PTh were separately coated on the fiber's surface, it was reported that the coatings of PAn and PTh had a morphology of agglomeration and partially coherent particles . In our study, the homogeneous polymer coating the fiber could be explained by the effect of the swelling of the PET in an organic solvent before polymerization on the incorporation of PAn and PTh on the PET fiber.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Moreover, no deformation was observed in the longitudinal image of the fiber. In the studies where PAn and PTh were separately coated on the fiber's surface, it was reported that the coatings of PAn and PTh had a morphology of agglomeration and partially coherent particles . In our study, the homogeneous polymer coating the fiber could be explained by the effect of the swelling of the PET in an organic solvent before polymerization on the incorporation of PAn and PTh on the PET fiber.…”
Section: Resultsmentioning
confidence: 49%
“…Moreover, these types of composites have attracted the attention of researchers due to them having potential applications in antistatic and electromagnetic interference shielding, electrochromic and heating devices . In the preparation of conductive textile composites, polyaniline (PAn), polythiophene (PTh) and polypyrrole have been the most commonly used polymers among other conjugated polymers . In the preparation of a conductive polymer/fiber composite, both PAn and PTh polymers are preferred due to them having superior properties.…”
Section: Introductionmentioning
confidence: 99%
“…Through synergic influence of polymers on nanomaterial composite, nanocomposites can add new properties such as: antibacterial [3], UV shielding, electrostatic charge dissipation, antistatic or conductive properties, water, oil, soil repellence, moisture management, flame retardancy, abrasion resistance, biocompatibility [4] etc. In the last years the use of conducting polymers [5][6] for flexible electronic textiles or leathers were studied and experimented using poly (3,4-ethylenedioxythiophene) [7], poly(fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, poly(pyrrole) [8], polycarbazole, polyindole, polyazepine, polyaniline [9], poly(thiophene) [10][11], and poly(p-phenylene)sulphide in combination with metals (iron, cobalt, nickel, copper, palladium, silver, platinum, gold) or carbon based materials (graphite, carbon nanotubes, and carbon black). Traditional textiles, both natural and synthetic, and leather materials are almost always insulators.…”
Section: Introductionmentioning
confidence: 99%
“…Different optical geometries such as single-mode fiber, multi-mode fiber, long-period fiber gratings (LPGs) or fiber Bragg gratings (FBGs) have been studied with the aim of increasing the sensitivity of the devices [5][6][7][8][9][10]. However, recent works have demonstrated that the use of nanodeposition techniques for the design of optical fiber sensors is becoming a hot topic in the fabrication of thin-film coated devices [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%